Immune activation and inflammation in lactating women on combination antiretroviral therapy: role of gut dysfunction and gut microbiota imbalance - Munjoma, Privilege Tendai; Chandiwana, Panashe; Wyss, Jacqueline; Mazhandu, Arthur John; Jordi, Sebastian Bruno Ulrich; Gutsire, Rutendo; Katsidzira, Leolin; Yilmaz, Bahtiyar; Misselwitz, Benjamin; Duri, Kerina (Frontiers in Immunology, 2023)
Introduction Combination antiretroviral therapy (cART) effectively controls HIV; however, chronic low-level viremia and gut microbiota dysbiosis remain significant drivers of gut and systemic inflammation. In this study, we explored the relationship between gut microbiota composition, intestinal inflammation, microbial translocation, and systemic inflammation in women on cART in Sub-Saharan Africa. Methods We conducted a study in HIV-infected and HIV-uninfected lactating women followed up at 6 weeks and 6 months postpartum in Harare, Zimbabwe. We used 16S ribosomal Ribonucleic Acid (rRNA) sequencing and MesoScale Discovery V-Plex assays to examine the gut microbiome and to quantify plasma inflammatory biomarkers, respectively. In addition, we measured fecal calprotectin, plasma lipopolysaccharide-binding protein (LBP), and soluble cluster of differentiation 14 (sCD14) by enzyme-linked immunosorbent assay to assess gut inflammation, microbial translocation, and monocyte/macrophage activation. Results A group of 77 lactating women were studied, of which 35% were HIV-infected. Fecal calprotectin levels were similar by HIV status at both follow-up time points. In the HIV-infected group at 6 weeks postpartum, fecal calprotectin was elevated: median (interquartile range) [158.1 µg/g (75.3–230.2)] in women who had CD4+ T-lymphocyte counts <350 cells/µL compared with those with ≥350 cells/µL [21.1 µg/g (0–58.4)], p = 0.032. Plasma sCD14 levels were significantly higher in the HIV-infected group at both 6 weeks and 6 months postpartum, p < 0.001. Plasma LBP levels were similar, but higher levels were observed in HIV-infected women with elevated fecal calprotectin. We found significant correlations between fecal calprotectin, LBP, and sCD14 with proinflammatory cytokines. Gut microbial alpha diversity was not affected by HIV status and was not affected by use of antibiotic prophylaxis. HIV significantly affected microbial beta diversity, and significant differences in microbial composition were noted. The genera Slackia and Collinsella were relatively more abundant in the HIV-infected group, whereas a lower relative abundance of Clostriduim sensu_stricto_1 was observed. Our study also found correlations between gut microbial taxa abundance and systemic inflammatory biomarkers. Discussion and conclusion HIV-infected lactating women had increased immune activation and increased microbial translocation associated with increased gut inflammation. We identified correlations between the gut inflammation and microbial composition, microbial translocation, and systemic inflammation. The interplay of these parameters might affect the health of this vulnerable population.